2014
DOI: 10.1063/1.4861941
|View full text |Cite
|
Sign up to set email alerts
|

A study of planar anchor groups for graphene-based single-molecule electronics

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
43
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 48 publications
8
43
1
Order By: Relevance
“…Somereviewsd evoted to the analysis of non-covalent interactions between aromatic compounds and graphene have been recently published. [9][10][11][12][13][14] Several theoretical studies have focused on the interactions between graphene and different heterocyclic aromatich ydrocarbons, such as benzene, [15][16][17][18][19][20][21][22][23][24][25] naphthalene, [18,21,[24][25][26] anthracene, [27] pentacene, [28] pyrene, [24,[27][28][29][30][31] coronene, [22,24,32] and ovalene. [22,24] It was established that these flat-structure molecules bind to graphene sheets in the planar stack orientation with the interaction energy whichi ncreases with the increasing intermolecular contact area.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Somereviewsd evoted to the analysis of non-covalent interactions between aromatic compounds and graphene have been recently published. [9][10][11][12][13][14] Several theoretical studies have focused on the interactions between graphene and different heterocyclic aromatich ydrocarbons, such as benzene, [15][16][17][18][19][20][21][22][23][24][25] naphthalene, [18,21,[24][25][26] anthracene, [27] pentacene, [28] pyrene, [24,[27][28][29][30][31] coronene, [22,24,32] and ovalene. [22,24] It was established that these flat-structure molecules bind to graphene sheets in the planar stack orientation with the interaction energy whichi ncreases with the increasing intermolecular contact area.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36] The interaction energy between aromatic hydrocarbonsa nd graphene increases upon substitution with both electron-donating and -withdrawing groups, as identified by DFT calculations. [25,27,28] It was shown that -CN and -OH groups added to anthracene and pyrene molecules are effectives ubstituents for enhancing binding to graphene. [27] It was determined that the binding energy is sensitive to the detailed atomica lignment of the substituent groups over the graphene sheet.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, these PAH molecules are mobile over the graphene surface at room temperature. 45 PAH-graphene contacts with high thermal stability may be fabricated by attaching suitable side groups onto the PAH molecules, an aspect requiring further investigations in the future.…”
Section: Discussionmentioning
confidence: 99%